Transcriptomic Analysis of Trichoderma atroviride Overgrowing Plant-Wilting Verticillium dahliae Reveals the Role of a New M14 Metallocarboxypeptidase CPA1 in Biocontrol - Morán-Diez, María E.; Carrero-Carrón, Irene; Rubio, M. Belén; Jiménez-Díaz, Rafael M.; Monte, Enrique; Hermosa, Rosa (Frontiers in Microbiology, 2019)
Verticillium dahliae, a vascular-colonizing fungus, causes economically important wilt diseases in many crops, including olive trees. Trichoderma spp. have demonstrated an effective contribution as biocontrol agents against this pathogen through a variety of mechanisms that may involve direct mycoparasitism and antibiosis. However, molecular aspects underlaying Trichoderma-V. dahliae interactions are not well known yet due to the few studies in which this pathogen has been used as a target for Trichoderma. In the present study, Trichoderma atroviride T11 overgrew colonies of V. dahliae on agar plates and inhibited growth of highly virulent defoliating (D) V. dahliae V-138I through diffusible molecules and volatile organic compounds produced before contact. A Trichoderma microarray approach of T11 growing alone (CON), and before contact (NV) or overgrowing (OV) colonies of V-138I, helped to identify 143 genes that differed significantly in their expression level by more than 2-fold between OV and CON or NV. Functional annotation of these genes indicated a marked up-regulation of hydrolytic, catalytic and transporter activities, and secondary metabolic processes when T11 overgrew V-138I. This transcriptomic analysis identified peptidases as enzymatic activity overrepresented in the OV condition, and the cpa1 gene encoding a putative carboxypeptidase (ID number 301733) was selected to validate this study. The role of cpa1 in strain T11 on antagonism of V-138I was analyzed by a cpa1-overexpression approach. The increased levels of cpa1 expression and protease activity in the cpa1-overexpressed transformants compared to those in wild-type or transformation control strains were followed by significantly higher antifungal activity against V-138I in in vitro assays. The use of Trichoderma spp. for the integrated management of plant diseases caused by V. dahliae requires a better understanding of the molecular mechanisms underlying this interaction that might provide an increase on its efficiency.